Beyond Straight Lines: Contextualizing Lobachevsky's Parallel Postulate Through the Geometry of the "Bubu" Fishing Gear - Abdurrobbil Falaq Dwi Anggoro; Wardono Wardono; Scolastika Mariani; Bambang Eko Susilo (Journal of Honai Math, 2025)
The axiom of Lobachevsky's parallelism is one of the topics that students often find difficult. The purpose of this research is to design a learning trajectory about the Lobachevsky axiom of parallelism using the context of a valid, practical and effective traditional fishing gear "bubu". This research applies development studies which consist of three main phases: preliminary study: analysis and exploration; prototype development: design and construction; and the last stage of assessment: evaluation and reflection. The results of the study show that the learning trajectory of the Lobachevsky equation axiom using the context of traditional fishing gear "bubu" is valid, practical and effective to improve problem-solving skills for mathematics education students. The conclusion is that there are six steps to the learning trajectory, namely: First, identification of problems with the local cultural context; Second: representation of problems; Third: make a settlement plan; Fourth: implementing the plan; Fifth: evaluate the solution of the problem; and lastly, make a conclusion about the axiom of Lobachevsky's parallelism.